Learning Trajectory of Dilation and Reflection in Transformation Geometry through the Motifs of Bamboo Woven - Maryati Maryati; Rully Charitas Indra Prahmana (Didaktik Matematika, 2021)
Cultural diversity around students can be integrated into learning mathematics in the classroom. Yet, Indonesian students still have difficulty applying mathematical concepts to solve problems related to everyday life, such as dilation and reflection in transformation geometry. Therefore, this study aims to design the dilation and reflection in transformation geometry learning trajectory using the motifs of bamboo woven. This context was used as the starting point in the learning process by applying the Pendidikan Matematika Realistik Indonesia approach. The research method used is design research consisted of three stages: preliminary design, teaching experiment, and retrospective analysis. This study describes how the motifs of bamboo woven made a real contribution for ninth-grade students to understand the concept of dilation and reflection in transformation geometry. The design experiments showed that this context can stimulate students to understand their knowledge of the idea of dilation and reflection in transformation geometry. All of the strategies and models that students find illustrate and discuss show how the construction or contribution of students can be used to help their initial understanding of the reflection and dilation.